2023
DOI: 10.3390/ijerph20054447
|View full text |Cite
|
Sign up to set email alerts
|

Disaster Preparedness and Awareness among University Students: A Structural Equation Analysis

Abstract: Students have long been among those most emotionally and physically affected by natural or manmade disasters, yet universities and colleges continue to lack effective disaster response and mitigation practices. This research identifies how students’ socio-demographics and disaster preparedness indicators (DPIs) impact their awareness of the dangers of disasters and their ability to survive and cope with the changes that disasters bring. A comprehensive survey was designed and distributed to university students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Our qualitative analysis identified three themes within the reviewed publications: college students' disaster literacy and preparedness, enhancing disaster education for students, and disaster impacts on college students' health, well-being, and education. Several studies examined students' disaster literacy and preparedness (Aksa et al 2020;Bhat et al 2017;Contreras 2014;Mızrak and Aslan 2020;Hasan et al 2022;Kılıç and Şimşek 2019;Patel et al 2020;Patel et al 2023;Piotrowski 2015;Sözen 2019;Zhang et al 2021). Many of these studies found that oftentimes, college students are ill-prepared for disasters and may not have the disaster literacy capacities to properly understand how to prepare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our qualitative analysis identified three themes within the reviewed publications: college students' disaster literacy and preparedness, enhancing disaster education for students, and disaster impacts on college students' health, well-being, and education. Several studies examined students' disaster literacy and preparedness (Aksa et al 2020;Bhat et al 2017;Contreras 2014;Mızrak and Aslan 2020;Hasan et al 2022;Kılıç and Şimşek 2019;Patel et al 2020;Patel et al 2023;Piotrowski 2015;Sözen 2019;Zhang et al 2021). Many of these studies found that oftentimes, college students are ill-prepared for disasters and may not have the disaster literacy capacities to properly understand how to prepare.…”
Section: Discussionmentioning
confidence: 99%
“…By integrating disaster risk management into curricula, educational programs prepare students to strengthen their values, sense of citizenship, and social sensitivity. As another example, Patel et al (2023) highlighted the influence of the university curriculum and emergency procedures on students' disaster awareness and preparedness, calling for enhanced programs and effective disaster risk reduction courses. Their study findings reveal that the university curriculum significantly impacts students' disaster awareness, while the establishment of university emergency procedures significantly affects students' disaster preparedness.…”
Section: Enhancing Disaster Preparedness Education In Higher Educationmentioning
confidence: 99%
“…Preparedness made before disasters significantly affects the effectiveness of the response and recovery phases (Patel et al, 2023). Kurt et al (2021) conducted a comprehensive study to determine whether individuals with special needs in Türkiye are prepared for earthquakes and their needs related to earthquake preparedness.…”
Section: Preparedness Before Earthquakesmentioning
confidence: 99%
“…One study identified functions such as governance, resources, risk reduction, funding acquisition, and time compression for the effective analysis of long-term housing recovery frameworks [20]. Another study derived 24 Disaster Preparedness Indicators and conducted a survey analysis of disaster preparedness awareness among university students [21]. Similarly, a survey-based study elucidated the functions affecting disaster resilience in the wake of storms and analysed their relative criticalities [22].…”
Section: Introductionmentioning
confidence: 99%